Ventricular septal defect recanalization in patients after total correction of Fallot tetralogy - Zinkovskyi, M. F.; Goryachev, A. G.; Dykuha, S. O.; Naumova, L. R.; Atamanyuk, M. Y.; Hondoga, V. M.; Pischurin, O. A.; Babadzanov, K. B.; Ivanov, Y. R. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Total correction of Fallot tetrology was performed in 1894 patients during the period 1980–2004 years. 680 (35,9%) patients were studied in remote period, 61(9,0%) of them had VSD recanalization. 16 (26,2%) patients of the latter group were submitted to reoperation-closure of recanalized VSD in terms of 1 month to 30 years after total correction of FT (8,5±3,3 г.). Pressure ratio in the right ventricle to systemic pressure after recanalized VSD closure decreased from 0,59±0,2 to 0,35±0,08. There were no lethal events. Good and satisfactory of patients (93.8%), their functional state corresponds to I-II FC NYNA classification. Positive dynamics of the volume and functional indices of the right and left heart ventricles were noted in all patients.